2022
DOI: 10.3390/ma15207386
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Mechanical Properties of Stress-Relieved AlSi10Mg Produced via Laser Powder Bed Fusion Additive Manufacturing

Abstract: The present study is dedicated to the evaluation of the mechanical properties of an additively manufactured (AM) aluminum alloy and their dependence on temperature and build orientation. Tensile test samples were produced from a standard AlSi10Mg alloy by means of the Laser Powder Bed Fusion (LPBF) or Laser Beam Melting (LBM) process at polar angles of 0°, 45° and 90°. Prior to testing, samples were stress-relieved on the build platform for 2 h at 350 °C. Tensile tests were performed at four temperature levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…[ 43 ] In contrast, the T6R OA –200T loses almost wholly the strain‐hardening ability due to the decrease in the strengthening effect of the Mg 2 Si precipitates induced by the high temperature. [ 24,28,37 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 43 ] In contrast, the T6R OA –200T loses almost wholly the strain‐hardening ability due to the decrease in the strengthening effect of the Mg 2 Si precipitates induced by the high temperature. [ 24,28,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the analysis of the true stress–true strain curves showed strain‐hardening phenomena only at temperatures below 200 °C. Lehmhus et al [ 24 ] observed comparable results on the SR alloy (2 h at 350 °C) tested at 125, 250, and 400 °C, reporting a significant reduction in strength above 250 °C and the dominant effect of temperature on building orientation. Tocci et al [ 25 ] shifted their attention on the L‐PBF AlSi10Mg alloy in AB condition and post‐thermal exposure (10 h at 100 and 150 °C), observing during high‐temperature tensile tests (100 and 150 °C) a slight decrease in UTS , a significant increase in e f , but no effect on YS.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, high-tech structural components in the transportation and energy industry are subjected to cyclic mechanical loads over a wide range of temperature distribution and mechanical load conditions [5]. Therefore, evaluating the effects of high temperatures on fatigue resistance is essential, particularly given the limited information in the literature [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the concurrent effect of defects content and heat treatment condition must be addressed. Furthermore, even though a few attempts to assess the high-temperature behavior of AlSi10Mg PBF-LB alloy have been carried out [ 21 , 22 , 23 , 24 ] to the best of the authors’ knowledge, mechanical properties at high temperatures of the A357 PBF-LB alloy have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%